In situ assay for analyzing the chromatin binding of proteins in fission yeast. - Kearsey, S; Brimage, L; Namdar, M; Ralph, E; Yang, X (2005)
An in situ technique for studying the chromatin binding of proteins in single fission yeast cells (Schizosaccharomyces pombe) is described. Cells are permeabilized by enzymatic digestion and extracted with a detergent-containing buffer. This procedure removes soluble proteins, but proteins that are bound to insoluble cell structures such as chromatin are retained, and overall cell morphology is maintained. Extraction of proteins is monitored by fluorescence microscopy, either using fluorescently tagged proteins or by indirect immunofluorescence. This method allows the chromatin association of proteins to be correlated with other cell cycle events without the need for cell synchronization.